Pre-lithiated silicon-based negative electrode material and preparation method and application thereof
Through the preparation method of prelithiated silicon-based anode material, the premixture of stable lithium metal powder and silicon powder and the use of additives such as perfluorooctyl ethyl acrylate is solved, and the interface damage of solid electrolyte caused by volume changes during charging and discharging of silicon-based anode material is achieved efficient conductivity and energy density.
Patent Information
- Application Number
- CN202411877268.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
AI Technical Summary
The existing silicon-based anode materials cause damage and regeneration of solid electrolyte interfaces due to volume changes during charging and discharging, resulting in low efficiency of active materials, and a conductive agent is needed to improve conductivity.
The prelithiated silicon-based negative electrode material preparation method is adopted, and the lithium fluoride additives induced by pre-mixing of stable lithium metal powder with silicon powder and adding perfluorooctylethylacrylate, etc., is formed by curing ultraviolet light to form an artificial protective layer to reduce the loss of electrolyte and lithium ions.
The maximum contact between each Si particle and the conductive active material is achieved, the binding energy between lithium ions and the negative electrode is reduced, the conductivity and energy density is improved, the expansion of the negative electrode and the decomposition of the electrolyte are reduced, and the solid electrolyte interface is stabilized.
Smart Images

Figure CN119695077A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and in particular relates to a pre-lithiated silicon-based negative electrode material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries (LIBs) have been widely studied as energy storage systems for portable electronic devices (such as mobile phones, laptops, and tablets) as well as electric vehicles (EVs) due to their high energy density, long cycle life, lack of memory effect, and self-discharge. Recently, the EV market has expanded with mandatory regulations for environmentally friendly vehicle use. The battery is the most important factor that determines the performance of EVs. In most cases, EVs with LIBs compete with internal combustion engine vehicles (ICEVs); therefore, LIBs must meet longer driving distances and faster charging times, which largely depends on their material systems.
[0003] As negative electrode materials, silicon-based and lithium-based materials have always attracted much attention. Compared with traditional carbon materials (typically graphite: 372mAh / g), silicon has the highest theoretical weight capacity (Li 4.4 Si is 4200mAh / g). Compared with other battery materials, silicon is also cheap, abundant and environmentally friendly, making it suitable for green electric vehicles. Due to these advantages, Si has become a popular negative electrode material. However, pure silicon negative electrodes have not yet been commercialized due to inherent problems. Silicon undergoes extreme volume changes (~300%) during charge and discharge. During this process, the solid electrolyte interface (SEI) is constantly damaged and regenerated, resulting in problems such as active material pulverization, shedding, and low initial coulombic efficiency (ICE). In addition, silicon is an insulator with an electrical conductivity of about 10 -5 S / cm. Although many studies have been conducted to overcome these fundamental challenges, they have only been partially addressed through the proposal of alternative materials.
[0004] Therefore, it is urgent to develop an innovative method to prepare a pre-lithiation silicon-based negative electrode material to comprehensively solve the structural and electrochemical problems. Summary of the invention
[0005] Based on the defects of the prior art, the first purpose of the present invention is to provide a method for preparing a pre-lithiated silicon-based negative electrode material; the second purpose of the present invention is to provide a pre-lithiated silicon-based negative electrode material prepared by the preparation method; the third purpose of the present invention is to provide an application of the pre-lithiated silicon-based negative electrode material in the preparation of lithium-ion batteries.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] In one aspect, the present invention provides a method for preparing a pre-lithiated silicon-based negative electrode material, the preparation method comprising the following steps:
[0008] Step 1: Mix perfluorooctyl ethyl acrylate (PFOEA) and 2-hydroxy-2-methylpropiophenone (HMPP), and add electrolyte to prepare a curing agent;
[0009] Step 2, premixing silicon powder and stabilized lithium metal powder (SLMP) in a pot mill to obtain a mixture;
[0010] Step 3, adding a curing agent to the mixture, then adding an electrolyte to adjust the solid content, and then adding 3-aminopropyltriethoxysilane to obtain a mixed suspension;
[0011] Step 4: After dispersing the mixed suspension, apply it on a copper foil and irradiate it with an ultraviolet lamp. The obtained sample is further dried to obtain a pre-lithiated silicon-based negative electrode material.
[0012] The present invention proposes a pre-lithiated silicon-based negative electrode material (SiLP). When SLMP and Si are mixed as a composite negative electrode material, the silicon negative electrode is partially lithiated without further treatment. This pre-lithiated Si maximizes the contact between each Si particle and the conductive active material, even if the negative electrode does not include a conductive agent such as carbon black, acetylene black and nanocarbon. Compared with bare silicon, pre-lithiation of Si ensures that sufficient lithium ions and electrons enter the silicon and reduces the binding energy of lithium ions with the negative electrode. The metallic properties of SLMP also improve the conductivity of silicon; SLMP can eliminate the need for conductive carbon additives. In addition, the use of SLMP can increase the energy density of LIB due to the reduced negative electrode potential. However, during the SEI formation process, the lower potential causes the electrolyte to decompose more easily. In order to stabilize the SEI, the present invention further introduces an additive perfluorooctyl ethyl acrylate that induces lithium fluoride (LiF). A method for stabilization and pre-lithiation is further proposed, using a fluorine (F)-rich material to form LiF before the electrolyte degrades. This step can minimize the electrolyte and Li + As a fluorinated polymer, perfluorooctyl ethyl acrylate (PFOEA) can be used to prepare an artificial protective SEI layer by ultraviolet (UV) curing, and PFOEA is used to stabilize the surface of lithium metal.
[0013] In the above preparation method, preferably, in step 1, the mass proportion of the perfluorooctyl ethyl acrylate in the curing agent is 2% to 8%.
[0014] In the above preparation method, preferably, in step 1, the mass proportion of the 2-hydroxy-2-methylpropiophenone in the curing agent is 0.5% to 5%.
[0015] In the above preparation method, preferably, the electrolyte is LiPF6 Solution.
[0016] In the above preparation method, preferably, the volume ratio of ethylene carbonate to diethyl carbonate is 1:1; the LiPF 6 The molar concentration of the solution is 1M.
[0017] In the above preparation method, preferably, in step 2, the mass ratio of the silicon powder to the stable lithium metal powder is 1:1 to 1:10.
[0018] In the above preparation method, preferably, in step 2, the rotation speed of the jar mill is 200 to 600 rpm / min; and the premixing time is 10 to 60 min.
[0019] In the above preparation method, preferably, in step three, the usage ratio of the mixture to the curing agent is 10 g: (0.1-10) mL.
[0020] In the above preparation method, preferably, in step three, electrolyte is added to adjust the solid content to 50% to 70%.
[0021] In the above preparation method, preferably, in step three, the mass proportion of the 3-aminopropyltriethoxysilane in the mixed suspension is 1% to 5%.
[0022] In the above preparation method, preferably, in step 4, the mixed suspension is dispersed by: first dispersing at a low speed of 300-600 rpm / min for 5-20 min; and then dispersing at a high speed of 1000-2000 rpm / min for 10-40 min.
[0023] In the above preparation method, preferably, in step 4, the ultraviolet light irradiation time is 10 to 200 seconds. Under the irradiation of the ultraviolet light, a specific chemical reaction will occur, wherein HMPP will decompose into free radicals, and the free radicals will react with PFOEA to form double bonds, thereby initiating a photo-crosslinking polymerization reaction.
[0024] In the above preparation method, preferably, in step 4, drying is carried out by first air drying and then vacuum drying; the air drying temperature is 30-80°C, and the drying time is 10-30 minutes; the vacuum drying temperature is 20-30°C, and the drying time is 10-30 minutes.
[0025] On the other hand, the present invention also provides a pre-lithiated silicon-based negative electrode material, which is prepared by the above-mentioned preparation method.
[0026] In another aspect, the present invention also provides the use of the above-mentioned pre-lithiated silicon-based negative electrode material in the preparation of lithium-ion batteries.
[0027] Beneficial effects of the present invention:
[0028] (1) In the method for preparing the pre-lithiated silicon-based negative electrode material of the present invention, the curing agent used contains a lithium fluoride (LiF)-inducing additive perfluorooctyl ethyl acrylate, which can minimize the electrolyte and Li + In addition, as a fluorinated polymer, perfluorooctyl ethyl acrylate (PFOEA) can be used to prepare an artificial protective SEI layer by ultraviolet (UV) curing. PFOEA is used to stabilize the surface of lithium metal. The product after photopolymerization on the negative electrode surface has a certain binder effect. No binder needs to be added to the negative electrode, and the bonding effect is good, which can inhibit the expansion of the Si negative electrode to a certain extent. The curing agent of the present invention is simple to prepare, and the photopolymerization reaction conditions are mild and the time is short.
[0029] (2) In the method for preparing pre-lithiated silicon-based negative electrode materials of the present invention, when SLMP and Si are mixed as a composite negative electrode material, the silicon negative electrode will be partially lithiated without further treatment. This pre-lithiated Si maximizes the contact between each Si particle and the conductive active material, even if the negative electrode does not include a conductive agent such as carbon black, acetylene black and nanocarbon. Compared with bare silicon, pre-lithiation of Si ensures that sufficient lithium ions and electrons enter the silicon and reduces the binding energy between lithium ions and the negative electrode. The metallic properties of SLMP also improve the conductivity of silicon; SLMP can eliminate the need for conductive carbon additives. In addition, the use of SLMP can increase the energy density of LIB due to the reduction of the negative electrode potential. The SEI film formed on the surface of the negative electrode sheet after the polymerization of SLMP and Si has good mechanical properties, which can block further contact between air and active metal Li and reduce side reactions.
[0030] (3) In the method for preparing the pre-lithiated silicon-based negative electrode material of the present invention, the UV lamp irradiation time is short and the process flow is simple; when the HMPP is irradiated with UV light, the HMPP will decompose into two types of free radicals, and under the UV light irradiation, the free radicals will react with acrylate to form a double bond. When the polymerization begins, the HMPP decomposes the free radicals and reacts with PFOEA to form a strongly cross-linked polymer network, and the reaction is exothermic, and the heat released will further accelerate the polymerization reaction.
[0031] (4) The pre-lithiated silicon-based negative electrode material of the present invention has a stable capacity and an improved first efficiency, and the Si particles do not expand rapidly during the continuous lithium insertion and extraction process.
[0032] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a detailed description of the preferred embodiments of the present invention in conjunction with the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0034] Figure 1 Schematic diagram of the process for preparing pre-lithiated silicon-based negative electrode material (SiLP) in Example 1 of the present invention.
[0035] Figure 2 This is a scanning electron microscope microscopic morphology comparison diagram of the pre-lithiated silicon-based negative electrode material (SiLP) prepared in Example 1 of the present invention and a conventional Si electrode.
[0036] Figure 3 This is a comparison chart of the rebound rates of the pre-lithiated silicon-based negative electrode material (SiLP) prepared in Example 1 of the present invention and the conventional Si electrode after different numbers of cycles.
[0037] Figure 4 This is a comparison chart of the cycle performance of the pre-lithiated silicon-based negative electrode material (SiLP) prepared in Example 1 of the present invention and a conventional Si electrode. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The process, conditions, reagents, experimental methods, etc. for implementing the present invention, except for the contents specifically mentioned below, are all common knowledge and common common sense in the art, and the present invention does not particularly limit the contents.
[0039] Embodiment 1:
[0040] This embodiment provides a pre-lithiated silicon-based negative electrode material and a preparation method thereof, such as Figure 1 As shown, the preparation method comprises the following steps:
[0041] (1) Use a pipette to transfer 310 μL of 97% pure perfluorooctylethyl acrylate (PFOEA) and 190 μL of 97% pure 2-hydroxy-2-methylpropiophenone (HMPP) into a beaker, and then add a specific electrolyte (1 M LiPF 6 EC:DEC (volume ratio of 1:1) electrolyte) was added until the total sample was 10 g, and the curing agent was obtained after mixing with a glass rod.
[0042] (2) Weigh 5 g of silicon powder and 5 g of stabilized lithium metal powder (SLMP, purchased from FMC Corporation, USA) into a 5 mL jar mill bottle, add zirconium beads and place in a jar mill for premixing. Set the parameters of the jar mill to 250 rpm / min and the time to 20 min to obtain a mixture.
[0043] (3) The premixed mixture was placed in a polytetrafluoroethylene cup, 500 μL of the curing agent prepared in step (1) was added dropwise to the mixture, and then 16.7 g of a specific electrolyte (1 M LiPF 6 The solid content of the electrolyte (EC:DEC (volume ratio of 1:1)) was adjusted to 60%, and then 780 μL of 99% pure 3-aminopropyltriethoxysilane (APTES) was added to obtain a mixed suspension.
[0044] (4) The mixed suspension was dispersed in a high-speed disperser. After dispersing at a low speed (speed of 500 rpm / min) for 10 min, the speed was adjusted to 1500 rpm / min again, and the suspension was taken out after high-speed dispersion for 30 min. The suspension was then coated on a copper foil with a 200 μm scraper, and then the ultraviolet lamp was turned on. The suspension was placed under the ultraviolet lamp for 150 s and then taken out.
[0045] (5) The sample was placed in a 35°C forced air oven for 10 minutes and dried for 20 minutes before being taken out to obtain a pre-lithiated silicon-based negative electrode material. When used, it was cut into 14 mm small discs using a cutting machine and placed in a glove box for standby use, and named SiLP.
[0046] Figure 1 This is a schematic diagram of the reaction of the pre-lithiated silicon-based negative electrode material in Example 1. Figure 1 (a) shows a schematic diagram of the reaction process of Si and Li metal powders and PFOEA; Figure 1 (b) shows a schematic diagram of the reaction of HMPP and PFOEA during the curing process. When HMPP is irradiated with ultraviolet light, HMPP will decompose into two types of free radicals. Under ultraviolet light, the free radicals will react with acrylates to form double bonds. When polymerization begins, the HMPP decomposes the free radicals and reacts with PFOEA to form a strongly cross-linked polymer network. The reaction is exothermic, and the heat released will further accelerate the polymerization reaction.
[0047] This embodiment also provides a method for assembling a lithium-ion battery using the pre-lithiated silicon-based negative electrode material (SiLP) prepared above, and the specific method is as follows:
[0048] (1) 10 g of lithium iron phosphate (LFP), conductive carbon black (SP) and polyvinylidene fluoride (PVDF) were weighed in a mass ratio of 8:1:1, and NMP was added to disperse and the solid content was adjusted to 60%. Then, the mixture was dispersed at 600 rpm for 5 min and then the speed was adjusted to 2000 rpm for high-speed dispersion for 30 min to obtain a mixed slurry, which was then coated on aluminum foil. The coated sample was placed in a 110°C forced air oven and dried for 2 h, then taken out, and then dried in a vacuum dryer for 1 h and cut into small discs to obtain an LFP electrode sheet, which was used as a positive electrode for standby use.
[0049] (2) Assemble the battery in a glove box, use the SiLP electrode prepared in Example as the negative electrode, and the LFP electrode prepared in step (1) as the positive electrode. Add a specific electrolyte (1M LiPF 6 EC:DEC (volume ratio of 1:1) electrolyte), after assembling the button battery, put it into a 25℃ oven for activation for 12 hours and then take it out for testing.
[0050] Comparative Example 1:
[0051] As a comparative example, a conventional Si electrode was used as the negative electrode, and the above-mentioned LFP electrode was used as the positive electrode. A specific electrolyte (1M LiPF 6 EC:DEC (volume ratio of 1:1) electrolyte), after assembling the button battery, put it into a 25℃ oven for activation for 12 hours and then take it out for testing.
[0052] Test experiment:
[0053] The lithium ion button battery prepared in Example 1 of the present invention was tested for button battery performance, and the specific testing process is as follows:
[0054] Stand for 2h→rate charge 0.1C, cut-off voltage is 4.5V→constant constant voltage charge, cut-off at 0.005A→constant current discharge 0.1C, voltage cut-off at 2.5V→stand for 10min→rate charge 0.1C, voltage cut-off at 4.5V→stand for 10min→constant voltage charge, current cut-off at 0.005A→constant current discharge 0.1C, voltage cut-off at 2.5V→stand for 10min→rate charge 0.1C, voltage cut-off at 4.5V→stand for 10min
[0055] The lithium ion button battery prepared in Comparative Example 1 was tested for button battery performance, and the specific test process was as follows:
[0056] Stand for 2h → Charge at a rate of 0.1C, cut-off voltage is 4.2V → Constant voltage charge, cut-off at 0.005A → Constant current discharge at 0.1C, voltage cut-off at 2.0V → Stand for 10min → Charge at a rate of 0.1C, voltage cut-off at 4.2V → Stand for 10min → Constant voltage charge, current cut-off at 0.005A → Constant current discharge at 0.1C, voltage cut-off at 2.0V → Stand for 10min → Charge at a rate of 0.1C, voltage cut-off at 4.2V → Stand for 10min
[0057] The test results are as follows Figure 2 to Figure 4 shown.
[0058] Figure 2 This is a scanning electron microscope microscopic morphology comparison diagram of the pre-lithiated silicon-based negative electrode material (SiLP) prepared in Example 1 of the present invention and a conventional Si electrode sheet; Figure 2 (a) is the microscopic morphology of the Si electrode; Figure 2 (b) in the figure is the microscopic morphology of the SiLP pole piece.
[0059] Depend on Figure 2 It can be seen that the pure Si pole piece has a clear boundary between each particle, indicating that the Si particles are in a separate state, which also indirectly shows that there is no electron and ion path for rapid charge transfer in the pure Si pole piece. In contrast, in the microscopic morphology of the SiLP pole piece, the boundary between adjacent particles has disappeared and become a whole. This overall process promotes the movement of charge because the connected active materials can form a path for transferring ions and electrons.
[0060] Figure 3 This is a comparison chart of the rebound rates of the pre-lithiated silicon-based negative electrode material (SiLP) prepared in Example 1 of the present invention and the conventional Si electrode after different numbers of cycles.
[0061] Depend on Figure 3 It can be seen that: with the increase of the number of cycles, the overall rebound rate of the electrode will gradually increase. When the cycle reaches 50 cycles, the rebound rate of pure Si reaches 39.8%, while the rebound rate of SiLP material is only 20.1%, which is close to the rebound rate of graphite. This further shows that in SiLP material, the macromolecular product generated by the curing reaction of PFOEA material and HMPP material has a strong bonding force, which can bond Li to Si. In the process of continuous lithium insertion and extraction, its bonding force ensures that Si particles do not expand rapidly.
[0062] Figure 4 This is a comparison chart of the cycle performance of the pre-lithiated silicon-based negative electrode material (SiLP) prepared in Example 1 of the present invention and the conventional Si electrode. The buckles are LFP||Si and LFP||SiLP material systems respectively.
[0063] Depend on Figure 4It can be seen that the initial capacities of Si and SiLP are 79 mAh g -1 (Si’s N / P ratio is 14.61) and 149 mAh g -1 (The N / P ratio of SiLP is 14.8). These results demonstrate the effect of using SLMP in combination with Si electrodes, with SiLP improving conductivity and Li-ion affinity. The capacity of silicon continued to decline; SiLP maintained a stable capacity during continued charge / discharge cycles. After 60 cycles, different capacity decline rates for silicon anode and SiLP composite anode batteries were demonstrated. In addition, a significant difference in first efficiency was confirmed, with the first efficiency level of 46% for the Si negative electrode and 70% for SiLP, which clearly shows that the first efficiency of the SLMP pre-lithiation electrode is improved.
[0064] The present invention uses specific embodiments to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A method for preparing a pre-lithiated silicon-based negative electrode material, characterized in that: The preparation method comprises the following steps: Step 1, mixing perfluorooctyl ethyl acrylate and 2-hydroxy-2-methylpropiophenone, and adding electrolyte to prepare a curing agent; Step 2, premixing silicon powder and stabilized lithium metal powder in a pot mill to obtain a mixture; Step 3, adding a curing agent to the mixture, then adding an electrolyte to adjust the solid content, and then adding 3-aminopropyltriethoxysilane to obtain a mixed suspension; Step 4: After dispersing the mixed suspension, apply it on a copper foil and irradiate it with an ultraviolet lamp. The obtained sample is further dried to obtain a pre-lithiated silicon-based negative electrode material.
2. The preparation method according to claim 1, characterized in that: In step 1, the mass percentage of the perfluorooctyl ethyl acrylate in the curing agent is 2% to 8%; Preferably, the mass proportion of the 2-hydroxy-2-methylpropiophenone in the curing agent is 0.5% to 5%.
3. The preparation method according to claim 1, characterized in that: The electrolyte is a LiPF6 solution of ethylene carbonate and diethyl carbonate; Preferably, the volume ratio of ethylene carbonate to diethyl carbonate is 1:1; and the molar concentration of the LiPF6 solution is 1M.
4. The preparation method according to claim 2, characterized in that: In step 2, the mass ratio of the silicon powder to the stable lithium metal powder is 1:1 to 1:10; Preferably, the rotation speed of the jar mill is 200 to 600 rpm / min; and the premixing time is 10 to 60 min.
5. The preparation method according to claim 1, characterized in that: In step three, the usage ratio of the mixture to the curing agent is 10 g: (0.1-10) mL.
6. The preparation method according to claim 5, characterized in that: In step 3, electrolyte is added to adjust the solid content to 50% to 70%; Preferably, the mass proportion of the 3-aminopropyltriethoxysilane in the mixed suspension is 1% to 5%.
7. The preparation method according to claim 1, characterized in that: In step 4, the mixed suspension is dispersed by first dispersing at a low speed of 300 to 600 rpm / min for 5 to 20 min; and then dispersing at a high speed of 1000 to 2000 rpm / min for 10 to 40 min.
8. The preparation method according to claim 1, characterized in that: In step 4, the ultraviolet light is used for 10 to 200 seconds; Preferably, the drying is carried out by air drying first and then vacuum drying; the air drying temperature is 30-80°C and the drying time is 10-30 minutes; the vacuum drying temperature is 20-30°C and the drying time is 10-30 minutes.
9. A pre-lithiated silicon-based negative electrode material, which is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the pre-lithiated silicon-based negative electrode material prepared by the preparation method according to any one of claims 1 to 8 or the pre-lithiated silicon-based negative electrode material according to claim 9 in the preparation of lithium-ion batteries.